(untitled) (Altre Modernità, 2024)
Paraphrasing the title of sociologist’s Albert Memmi’s famous essay, the paper aims to focus on the construction of indigenous identity in the works of artists and writers coming from the Arctic territories of Canada. In particular, we would like to highlight the use of autofiction to build counter-narratives and as a tool of self-decolonization, as well as the numerous references to indigenous mythology, cosmogonies, and—most importantly—the implied return to cultural practices which were at the very center of Canada’s governmental campaigns of assimilation and reformation of indigenous youth. Through the analysis of the novel Split Tooth (2018) by Inuk musician and artist Tanya Tagaq, we intend to point out the systemic violence of indigenous communities, heirloom of a colonial identity, and the conscious rejection of this incoherent and broken identity through practices of cultural reappropriation and reclamation. Following the fil rouge of an ethnocultural and intermedial perspective, rooted in a long tradition of oral storytelling, thus intrinsically hybrid, we will find confirmation of the same practices in other and different narratives originating in the Arctic area of Canada, such as the short story collection of dene writer Richard Van Camp, Moccasin Square Gardens (2019), which use magical realism, autofiction and cultural practices based on oral storytelling to operate a patient and careful reconstruction of their own indigenous identity; decolonizing themselves to support the decolonization of younger generations.